Computing Powers of Positive Integers Using the Modified Detached Coefficients Method and the Staircase Method. - Avoka, John (2014)
A Thesis presented to the Department of Mathematics, Kwame Nkrumah University of Science and Technology in Partial Fulfillment of the Requirements for the Degree of